Catholic Civics Education in the Early Cold War: Zeal for Democracy, Zeal for Christ. Issue 4 (7th September 2022) - McCamant, Jane
Abstract: In the late 1940s and 1950s American Catholic educators faced the dilemma of how to transmit Catholic faith and culture to the next generation while also reassuring their non‐Catholic neighbors that they were fully American in lifestyle and loyalties. This article examines one response to that dilemma: the convergence of public and Catholic school civics curricula through the widespread use of experiential pedagogy in Catholic civics education. Using a content analysis of civics textbooks and teacher's guides from both school systems, this article demonstrates how both kinds of schools converged on an experiential style of civics education, despite vocal opposition to "progressive" pedagogy at elite levels of Catholic educational discourse. The article then presents a partial explanation for this dissonance, demonstrating the moral certainty exhibited in the same Catholic‐school textbooks, and suggesting that Catholic educationists understood American Catholics to be morally privileged in a way that gave them special insight into American democracy and protected them from the negative influences of secular educational philosophy. This case study speaks to larger questions of how organizations manage conflicts between abstract principles and practical action, and suggests the value of including religious schools in the sociological study of "loose coupling" in educational organizations.